2006
DOI: 10.1128/aac.00763-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of the Novel Oxazolidinones DA-7867 and DA-7157 against Rapidly and Slowly Growing Mycobacteria

Abstract: DA-7867 and DA-7157 are oxazolidinones active against pathogenic aerobic actinomycetes including Nocardia spp. and Mycobacterium tuberculosis. However, the activity of these drugs against nontuberculous mycobacterium (NTM) species is not known. In this work, we compared the susceptibilities of 122 clinical isolates and 29 reference species of both rapidly growing and slowly growing mycobacteria to linezolid, DA-7867, and DA-7157 by the broth microdilution method. The MICs for 50 and 90% of the strains tested (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…In the present study, linezolid demonstrated similar activities against most mycobacterial isolates in agreement with previous reports (5,6). However, the M. avium complex and M. abscessus required 32 mg/L to inhibit 90z of the isolates tested, indicating that treatment with linezolid against these two species is difficult.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, linezolid demonstrated similar activities against most mycobacterial isolates in agreement with previous reports (5,6). However, the M. avium complex and M. abscessus required 32 mg/L to inhibit 90z of the isolates tested, indicating that treatment with linezolid against these two species is difficult.…”
supporting
confidence: 80%
“…In the second-line drugs, the highest drug resistance rate was to PAS (91.5z), followed by ofloxacin (69.2z), while the lowest resistant rates were for amikacin and capreomycin. Linezolid showed excellent activity against M. kansasii, and M. fortuitum, with MIC ranges of 0.5-1 mg/L and 0.5-8 mg/L, respectively, which was in accordance with previous reports (5,6). Similarly, the in vitro activities of sy142 and sy144 against these two species were comparable to those of linezolid.…”
supporting
confidence: 78%
“…bolletii (MIC of 0.12 g/ml for TZD compared with 0.5 g/ml for LZD). The 2006 study also reported 17 isolates of M. chelonae complex, but again the species were not differentiated (i.e., M. chelonae and M. immunogenum) as in this study (5).…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, the 2006 study showed a single isolate of M. terrae complex (not identified to the species level) with a TZD MIC of 1 g/ml compared with 16 g/ml with LZD (5). Six isolates of M. simiae in the 2006 study exhibited a TZD MIC range of 1 to 8 g/ml and an LZD MIC range of 8 to 32 g/ml (MIC 50 s were not given [5]) compared with the TZD MIC range of 1 to Ͼ32 g/ml (MIC 50 , 8 g/ml) and an LZD MIC range of 8 to 128 g/ml (MIC 50 , 64) of eight isolates in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation